L’introduzione del vaccino anti-HPV bivalente adiuvato con AS04 nelle regioni italiane: impatto economico ed effetti sulla salute delle donne - Cavallo, Maria Caterina; Cipriani, Filippo; Gerzeli, Simone; Demarteau, Nadia; Marocco, Alessia; Bamfi, Francesco (Farmeconomia. Health economics and therapeutic pathways, 2008)
Introduction: the impact of cervical cancer prevention, in particular through HPV female vaccination, has been published for many countries at the national level. However, to our knowledge no attempt has been made to address the impact at a regional level. Since the Italian health reforms of the early 1990s, introducing “managerialism”, decentralization and quasi-market mechanisms, regional authorities have consequently been experimenting with different organizational and funding models to achieve an acceptable combination of equity, efficiency, freedom of choice and cost-containment. Methods: a Markov model, previously described and successfully adapted to the national scenario [La Torre, 2007], has been used to explore the impact of preventive cervical cancer vaccination with Cervarix™ at a regional level in Italy. Resource use was based on a standard therapeutic path applied to all regions. However we quantified the impact of the so-called “decentralization progress” by collecting regional data on: pap-test coverage, tariffs for treatments and cost of the vaccination course. We performed for each Italian region a cost-effectiveness analysis combined with a regional budget impact analysis. The regional analyses compared HPV vaccination, both of a single female cohort (12 years old) and a multiple female cohort (12+16 years old), plus screening to screening only. Results: 21 regional reports were produced presenting regional results on screening coverage, treatments costs, ICER and ICUR, net cost per subject vaccinated etc. Conclusions: national and regional analyses have two different aims: the former wants to address national regulatory agencies and needs to be representative of the national population whereas the latter deals with the real budget-holders, accountable in the eyes of patients. Furthermore in the Italian scenario, characterized by decentralization and local autonomy, a further level of detail is essential in order to describe the specific local settings and implications of a new health intervention.